Digital-Based Academic Supervision Model in Improving Teacher Performance at Madrasah SMP Negeri 1 Seputih Banyak - Lilis Haryati; Rina Mida Hayati; Agus Setiawan (CV. Bimbingan Belajar Assyfa, 2025)
The rapid development of digital technology has fundamentally transformed various sectors, including education, yet many madrasahs in Indonesia still face challenges in implementing effective academic supervision due to limited digital infrastructure, low technological literacy among supervisors, and the absence of structured digital supervision models. This study aims to analyze the implementation of a digital-based academic supervision model and its impact on improving teacher performance at Madrasah SMP Negeri 1 Seputih Banyak, Central Lampung Regency. Using a qualitative case study approach, data were collected through in-depth interviews with the madrasah head, supervisors, and teachers, participatory observation of supervision practices, and documentation of supervision activities and teacher performance records. The findings reveal that the digital-based academic supervision model is implemented through four strategic stages: digital planning and scheduling, technology-assisted classroom observation, data-based feedback and reflection, and sustainable professional development follow-up. The integration of digital tools such as the Madrasah Digital Report (RDM), Google Classroom, and video-based observation has significantly improved efficiency, transparency, and teacher engagement in supervision. This model contributes to measurable improvements in teacher performance, including enhanced lesson planning, more effective classroom management, increased use of technology in teaching, and improved student learning outcomes. However, challenges such as limited internet access, varying levels of teacher digital competence, and time constraints remain significant obstacles. This study concludes that the digital-based academic supervision model offers a transformative approach to improving teacher performance in madrasahs, provided that adequate infrastructure, continuous training, and strong leadership commitment are in place. These findings provide a practical framework for other madrasahs seeking to leverage digital technology for academic supervision and teacher professional development.